2009
DOI: 10.1111/j.1439-0531.2009.01446.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Maturation in Canine Foetuses From Early Pregnancy to Parturition

Abstract: Development of the foetal respiratory system includes both pulmonary growth and maturation. In human medicine, a higher incidence of respiratory distress is reported in newborn males. This study aimed to identify different phases of canine foetal lung maturation throughout pregnancy, to determine the stage of pregnancy in which surfactant production begins and to compare pulmonary development of male and female foetuses. Pregnant bitches (34) were subjected to elective ovariohysterectomy and allocated into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 4 publications
(6 reference statements)
0
18
0
1
Order By: Relevance
“…The expiratory volume of the maximal forced‐expiration state was set at 10 mL/kg, lower than 15 mL/kg used in the earlier study with Beagle dogs . The baseline was lowered because the body‐condition scores of brachycephalic dogs were higher than those of Beagle dogs, and obese dogs have a lower functional residual capacity than normal dogs . Respiration was controlled manually using the reservoir bag of the anesthetic machine.…”
Section: Methodsmentioning
confidence: 99%
“…The expiratory volume of the maximal forced‐expiration state was set at 10 mL/kg, lower than 15 mL/kg used in the earlier study with Beagle dogs . The baseline was lowered because the body‐condition scores of brachycephalic dogs were higher than those of Beagle dogs, and obese dogs have a lower functional residual capacity than normal dogs . Respiration was controlled manually using the reservoir bag of the anesthetic machine.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the size of the dog lung, it has also been possible to show that the maturation of the lung during in utero development occurs in a radial fashion with the lung units associated with the upper airway being more developed than those of the distal lung (Sipriani et al, 2009). There is a gap in our knowledge of normal lung morphology in the first months of life in dogs as most studies looking at the association between age and lung structure begin from approximately 6e12 months of age.…”
Section: Dogsmentioning
confidence: 97%
“…At term the dog lung is in a relatively immature state, has not yet entered the alveolar stage of development, and has a distinctly saccular morphology (Sipriani et al, 2009), in contrast to humans where alveolarization has clearly begun at birth. Interestingly, while the absolute number of studies on the normal aging of the canine lung is relatively low compared to other species, the breadth of ages where we have some data spans all ages from the in utero period and into senescence.…”
Section: Dogsmentioning
confidence: 99%
“…Sipriani et al. () observed the lung development of canine foetuses throughout gestation and found that the pseudoglandular phase occurred between gestational days 35 and 46 and that the onset of the canalicular and saccular phases began on gestational days 48 and 56, respectively, whereas alveolar development began only after birth and extended throughout the neonatal period.…”
Section: Foetal and Neonatal Pulmonary Development And Maturitymentioning
confidence: 99%
“…This process begins early in gestation and extends into adulthood, and it can be divided into five developmental phases: embryonic, pseudoglandular, canalicular, saccular and alveolar (Miyoshi et al 1998). Sipriani et al (2009) observed the lung development of canine foetuses throughout gestation and found that the pseudoglandular phase occurred between gestational days 35 and 46 and that the onset of the canalicular and saccular phases began on gestational days 48 and 56, respectively, whereas alveolar development began only after birth and extended throughout the neonatal period.…”
Section: Foetal and Neonatal Pulmonary Development And Maturitymentioning
confidence: 99%